Is Heathcliff a Murderer? Puzzles in 19th Century Fiction - Sutherland, John (Oxford University Press, 1996)
In this quirky and intriguing book, John Sutherland has conveniently gathered together thirty-four nagging little questions, puzzles, errors, and enigmas from some of the best-loved examples of Victorian fiction. Readers often have stumbled upon seeming mysteries in their favorite novels. Why, for example, is the plot of The Woman in White irrevocably flawed? (The timing of the crime is off.) Is the hero of George Eliot's Middlemarch illegitimate? (Probably, although he was later legitimized.) Why does the otherwise sensible Jane Eyre give in to a sudden and unexplained outburst of superstition? (Charlotte Bronte, in reality, had a similar experience.) What is the real reason we find The Picture of Dorian Gray so disturbing? (There is an overwhelming emphasis on the sense of smell.) These answers and more can all be found in John Sutherland's entertaining and maddening book.
Keywords: English Fiction - 19th Century - History and Criticism